2016
DOI: 10.1007/s11010-016-2760-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidase facilitates osteogenic differentiation and mineralization of embryonic stem cells through the activation of Nrf2 and ERK signal transduction pathways

Abstract: Nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/heme oxygenase-1 (HO-1) signal is known to play important roles in controlling bone homeostasis. This study examined how oxidative stress affects the mineralization of embryonic stem (ES) cells by exposing them to glucose oxidase (GO), which continuously generates H2O2 at low concentrations. The roles of Nrf2/HO-1 and mitogen-activated protein kinases on osteogenesis in GO-exposed ES cells were also investigated. GO treatment at relatively low concentrations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…It is well recognized that Runx2 plays a key role in osteoblastic differentiation and bone formation. Nrf2 is reported to positively regulate the expression of Runx2 (Sim et al, 2016). Therefore, our finding suggested that Nrf2 stabilization and activation mediated the protective effects of Cur on the viability and differentiation of osteoblasts.…”
Section: Discussionsupporting
confidence: 50%
“…It is well recognized that Runx2 plays a key role in osteoblastic differentiation and bone formation. Nrf2 is reported to positively regulate the expression of Runx2 (Sim et al, 2016). Therefore, our finding suggested that Nrf2 stabilization and activation mediated the protective effects of Cur on the viability and differentiation of osteoblasts.…”
Section: Discussionsupporting
confidence: 50%
“…However, mild oxidative stress can activate a protective mechanism via the NRF2 signaling pathway, while high ROS accumulation activates a stress signal related to cell death rather than survival 42 . Additionally, according to the previous report 43 , NRF2 signaling is activated in response to ROS and regulates bone metabolism positively or negatively depending on the degree of oxidative stress. NRF2 signaling positively controls bone homeostasis by maintaining an intracellular redox balance, whereas NRF2 may negatively regulate cellular differentiation to osteoblasts through inhibition of the Runx2-dependent transcriptional activity.…”
Section: Discussionmentioning
confidence: 89%
“…For example, studies in vitro using rodent vascular smooth muscle cells show that dimethyfumarate or resveratrol could attenuate the deposition of a mineralised matrix and suggest protection against oxidative stress-induced mitochondrial damage, via activation of Nrf2 and SIRT1 signaling and downregulation of osteogenic transcription factors [ 126 , 127 ]. In contrast, glucose-induced oxidative stress enhances the osteogenic differentiation and mineralisation of human embryonic stem (ES) cells, by the upregulation of runt-related transcription factor 2 (Runx2), Nrf2, and HMOX1, which was inhibited by Nrf2 knockdown [ 128 ] highlighting a context-specific regulation of the calcification process. Given the links between Nrf2 and bone homeostasis, it is not surprising to have an association between Nrf2 signaling and vascular calcification.…”
Section: Nrf2 In Vascular Calcificationmentioning
confidence: 99%